THE MEMORY OF THE EARTHQUAKE OF 1647 IN THE WORK OF LIBERAL HISTORIANS - López Taverne, Elvira (Revista de Historia Social y de las Mentalidades, 2012)
The memory of the earthquake of 1647 is strongly tied to the writings of XIX century liberal historians. This relationship between memory and historical testimony permeates the discussion on the historical recovery from this catastrophe. By critically analyzing the historiographical work of liberal authors, the present paper proposes the construal of the earthquake as a central event in colonial times, the rereading of Baroque religiosity and the role of the Church in that period, and the reinterpretation of the miracle by the Christ of May.
Keywords: Chile; Earthquake of 1647; Liberal Historiography; Historic Memory